Master slave husband wife : an epic journey from slavery to freedom - Woo, Ilyon (New York : Simon & Schuster, 2023)
Presents the remarkable true story of Ellen and William Craft, who escaped slavery through daring, determination, and disguise, with Ellen passing as a wealthy, disabled white man and William posing as "his" slave
In December 1848, a young enslaved couple named Ellen and William Craft traveled openly by rail, coach and steamship from Macon, Georgia, to Philadelphia, Pennsylvania. Ellen, who passed for white, disguised herself as a wealthy disabled man, with William as "his" slave. Woo follows their journey north, and in joining the abolitionist lecture circuit. When the new Fugitive Slave Law in 1850 put them at risk, they fled from the United States. Their very existence challenged the nation's core precepts of life, liberty, and justice for all. -- adapted from jacket
Overture -- Macon -- Georgia -- Savannah -- Charleston -- Overland -- Pennsylvania -- New England -- The United States -- Canada -- Overseas -- Coda
Includes bibliographical references (pages 343-391) and index
Keywords: Craft, William; Craft, Ellen; Fugitive slaves -- United States -- Biography; Fugitive slaves -- England -- Biography; Slaves -- Georgia -- Biography; Racially mixed women -- United States -- Biography; Abolitionists -- United States -- Biography; Antislavery movements -- History -- 19th century; Biographies